Noninvasive Brain Stimulation & Space Exploration: Opportunities and Challenges. (December 2020) - Romanella, S.M.; Sprugnoli, G.; Ruffini, G.; Seyedmadani, K.; Rossi, S.; Santarnecchi, E.
Highlights: Astronauts undergo spaceflight associated brain modifications, psychological stress, and changes in cognitive performance. Noninvasive brain stimulation has been used as a portable, safe countermeasure to a variety of stressors. Ad-hoc protocols could enhance in-flight performance, boost executive functions, sleep efficiency and mood. Plasticity-based protocols could accelerate pre-flight Earth-based training and capture post-flight changes. Abstract: As NASA prepares for longer space missions aiming for the Moon and Mars, astronauts' health and performance are becoming a central concern due to the threats associated with galactic cosmic radiation, unnatural gravity fields, and life in extreme environments. In space, the human brain undergoes functional and structural changes related to fluid shift and changes in intracranial pressure. Behavioral abnormalities, such as cognitive deficits, sleep disruption, and visuomotor difficulties, as well as psychological effects, are also an issue. We discuss opportunities and challenges of noninvasive brain stimulation (NiBS) methods — including transcranial magnetic stimulation (TMS) and transcranial electrical stimulation (tES) — to support space exploration in several ways. NiBS includes safe and portable techniques already applied in a wide range of cognitive and motor domains, as well as therapeutically. NiBS could be used to enhance in-flight performance, supporting astronauts during pre-flight Earth-based training, as well as to identify biomarkers of post-flight brain changes for optimization of rehabilitation/compensatory strategies. We review these NiBS techniques and their effects on brain physiology, psychology, and cognition.